“Dissecting the paradox: spirituality and yoga in mental wellbeing.” - Douglas, Linda (Journal of spirituality in mental health, 2025)
This research critically examines the intricate interplay between spirituality and yoga, assessing their collective impact on mental wellbeing. Amidst yoga’s transcultural proliferation, transcending its indigenous spiritual roots, this study probes the intricacies inherent in its adaptation as a mental health intervention. The research utilizes qualitative and ethnographic methodologies to dissect yoga’s therapeutic efficacy, juxtaposing its spiritual genesis with secular manifestations. Central to this analysis is the exploration of whether the secularization of yoga practices dilutes or maintains their therapeutic potential. Navigating the nuanced dynamics from both global and Indian perspectives, this study contributes to a sophisticated understanding of yoga’s evolving role within contemporary mental health paradigms. By examining the paradoxical coexistence of spiritual and secular dimensions in yoga, the research aims to inform and enhance mental health service frameworks, addressing a significant lacuna in current mental health discourse.